Performance Analysis of Underlaid Full-Duplex D2D Cellular Networks - Hung V. Vu; Tho Le-Ngoc (IEEE Access, 2019)
This paper investigates the benefits of incorporating underlaid full-duplex (FD) device-to-device (D2D) communications into cellular networks. Toward this end, we provide an analytical performance characterization of underlaid D2D cellular networks where D2D users operate in FD mode under the presence of residual self-interference. In considered networks, the base-stations (BSs) are distributed according to a hexagonal grid, while the locations of cellular and D2D users follow Poisson point processes (PPPs). Based on the stochastic-geometry approach, we develop the approximations of key performance metrics including coverage probabilities and achievable sum-rates of both cellular and D2D links, and such approximations involve quickly commutable integrals. Under a special case in which the number of D2D links is sufficiently large, the obtained approximations can be simplified to closed-form expressions, allowing characterize the sum-rate behaviors under the effects of various system parameters. We show that underlaid D2D communications in cellular network can offer a significant spectral efficiency gain as compared to pure cellular transmission. With a sufficiently low self-interference cancellation level, FD D2D can offer substantial spectral efficiency improvement over the half-duplex (HD) counterpart. Finally, the resulting performance metrics are compared with multi-cell networks operating in standard and fractional frequency reuse modes, and observe that frequency reuse provides improved coverage probabilities of both cellular and D2D links, but substantially reduces the D2D sum-rate performance.